Metastases to pancreas diagnosed by endoscopic ultrasound-guided fine-needle aspiration: A case series and review of imaging and cytologic features - Caballero Malacara, Valeria; Luna Limón, Claudia Gabriela; Barboza Quintana, Oralia; Gómez Macías, Gabriela Sofía (BioMed Central, 2023)
Fine-needle aspiration (FNA) is ideal for the diagnosis of pancreatic neoplasms with high precision. We described five cases of metastases to the pancreas, highlighting the importance of clinical data, imaging features and the use of immunocytochemistry to lead the diagnosis. We retrospectively searched our archives for metastatic neoplasm to the pancreas diagnosed with FNA performed with endoscopic ultrasound, over a 5-year period. Furthermore, we reviewed the literature for imaging and cytologic features. We described five cases of metastatic neoplasms, a renal cell carcinoma, a breast carcinoma, one leiomyosarcoma, a hepatocellular carcinoma, and ovarian serous carcinoma. All of them has history of primary malignancy and were confirmed with immunostains. All the patients were asymptomatic and identified the metastasis during the follow-up, except for the ovarian serous carcinoma were the patient had acute abdominal pain, and the most common imaging feature were the irregular borders. Although the metastases to pancreas are rare, its important to always have the history of the patient, imaging features, and the suspicion at the moment of the evaluation of the smears and cell-block, because the management and prognostic its different compared to primary malignancies.